PELATIHAN MANUFACTURING TOOLS ORNAMEN TERALIS BAGI KARYAWAN BENGKEL LAS GESEK MENYALA DI DISTRIK HERAM KOTA JAYAPURA - Ranteallo, Obet; Joni, Joni; Palamba, Pither; P. Siregar, Samuel (LPPM Universitas Bina Bangsa, 2025)
The welding workshop industry is one of the sectors that continues to grow along with the increasing demand for security and aesthetics in buildings, both residential and commercial. Window grilles and fences are two main components that not only function as protection but also as decorative elements that can add aesthetic value to a building. Therefore, it is important for welding workshop employees to have adequate skills and knowledge in making window and fence trellis ornaments. The purpose of this service is: Improving the technical skills of friction welding workshop employees in making window and fence trellises with various ornamental designs; including 90 degree angle metal welding guides, star-shaped tools, and zig-sag. The service methods used: Theory and Introduction, namely an introduction to the importance of ornaments in window and fence trellises, the history and evolution of design, and the basic theory of making ornaments; Field Practice, namely employees will be directly involved in the process of making the ornaments. This stage includes cutting, welding, and forming materials according to the desired design; Design Development, namely participants/employees are taught drawing techniques and designing ornamental designs using simple drawings; Final Project, namely each participant/employee will create a final project in the form of a window or fence trellis with an ornamental design that has been taught during the training. As a result, the service team has provided skills to the employees of the friction welding workshop in making window and fence trellis ornament tools, including 90 degree angle metal welding guides, star-shaped tools, and zig-zags